2013
DOI: 10.1159/000350412
|View full text |Cite
|
Sign up to set email alerts
|

Functional Retinal Impairment in Type 1 Diabetic Patients without any Signs of Retinopathy

Abstract: Purpose: To investigate functional and morphological retinal changes in the long-term follow-up in subjects with type 1 diabetes mellitus (DM1) without any signs of retinal vasculopathy. Methods: Functional testing included Humphrey Matrix perimetry (30-2 threshold program) and white-on-white Humphrey perimetry (HFA, 30-2 SITA standard), while retinal nerve fibre layer (RNFL) thickness was measured by scanning laser polarimetry with variable corneal birefringence compensator. Results: Data from 20 eyes of 20 s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
2
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 18 publications
1
2
0
Order By: Relevance
“…20 Our previous research shows that the higher the serum IL-17A level, the higher the incidence and severity of DR. The underlying mechanism can be summarized as: (1) IL-17A can trigger the destruction of the fundus vascular barrier as well as increase the degree of inflammation of 10 Global DR research studies have revealed that a longer T2DM duration, increasing age, higher HbA1c levels, and poorer blood pressure control were strongly correlated with DR. 13,22 In this study, the longer the DM duration, the higher the prevalence and severity of DR, which is consistent with previous studies. 23 Many previous studies have shown that FCP is related to DR. 24 An earlier study showed that after adjustment for confounding factors, C-peptide and insulin levels were significantly correlated with extent of DR in Latinos with type 2 diabetes.…”
Section: Discussionsupporting
confidence: 92%
“…20 Our previous research shows that the higher the serum IL-17A level, the higher the incidence and severity of DR. The underlying mechanism can be summarized as: (1) IL-17A can trigger the destruction of the fundus vascular barrier as well as increase the degree of inflammation of 10 Global DR research studies have revealed that a longer T2DM duration, increasing age, higher HbA1c levels, and poorer blood pressure control were strongly correlated with DR. 13,22 In this study, the longer the DM duration, the higher the prevalence and severity of DR, which is consistent with previous studies. 23 Many previous studies have shown that FCP is related to DR. 24 An earlier study showed that after adjustment for confounding factors, C-peptide and insulin levels were significantly correlated with extent of DR in Latinos with type 2 diabetes.…”
Section: Discussionsupporting
confidence: 92%
“…In addition to inner retinal thinning, functional deficits in contrast sensitivity, perimetry testing, multifocal electroretinogram (mfERG), and dark adaptation have also been described in diabetic patients without DR or with very early DR [8][9][10][11][12][13]. A correlation between GCL thinning and visual field deficits on Rarebit perimetry was demonstrated in type 1 DM patients with no DR [14].…”
Section: Evidence For Retinal Neurodegeneration In Pre-clinical Drmentioning
confidence: 99%
“… 11 13 Contrast sensitivity is a nonspecific test of the inner retina, but different spatial frequencies favor specific neural pathways. 14 , 15 Parravano et al 16 , 17 showed that performance on multiple tests of inner retinal function, including FDP and SAP, is reduced in subjects with diabetes without evidence of DR. Additionally, Jackson et al 18 demonstrated that reduced contrast sensitivity and decreased performance on FDP and SAP correlate with nonproliferative diabetic retinopathy (NPDR). Hellgren et al 19 evaluated performance on SAP over 4 years and demonstrated progression of DR based on neuroretinal functioning and not microvascular-based grading.…”
mentioning
confidence: 99%